Polidocanol monotherapy for a superficial orbital venous malformation in a horse. (1st June 2022) - Stonex, Tara M.; Zibura, Ashley E.; Andres, Michael; Gilger, Brian C.; Oh, Annie
Abstract: Objective: To describe the use of 1% polidocanol as the sole treatment for a superficial orbital venous malformation in a horse. Animal: A 23‐year‐old Welsh Cobb cross gelding with a distensible swelling affecting the left lower eyelid, and secondary palpebral margin abnormalities and superficial keratitis. Procedure: Color flow Doppler ultrasonography revealed non‐pulsatile blood flow within the tortuous vascular network most consistent with a superficial orbital venous malformation appearing to involve the lateral palpebral and transverse facial veins. An intravenous catheter was placed within the lateral aspect of the venous malformation, and agitated saline was slowly injected into the vessel while simultaneously ultrasound imaging the medial aspect in which the bubbles were observed coursing across, consistent with lateral to medial flow. Contrast venography confirmed a corkscrew vessel along the ventral aspect of the orbital rim. Under standing sedation, 1% polidocanol solution was administered slowly through the intravenous catheter while manual pressure was applied on the medial and lateral aspects of the venous malformation. Results: Ultrasonography performed immediately after administration of polidocanol confirmed venous stasis, and formation of a thrombus. No adverse side effects were noted. The venous malformation and associated palpebral margin abnormalities and superficial keratitis resolved at the time of re‐examination at 4 months. Conclusion and Clinical Relevance: Polidocanol as the sole treatment for a superficial orbital venous malformation in a horse was well tolerated and led to clinical resolution. Sclerosant monotherapy may be a safe treatment option for superficial orbital venous malformations.